ANALYSIS OF MULTIPLICATION LEARNING DIFFICULTIES IN STUDENTS - Azzizah, Fitri Nur; Amaliyah, Aam; Amalia, Rizki; Muflihah, Zahwa (Transpublika Publisher, 2022)
Mathematics is the foundation of all sciences. Due to this reason, mathematics will never be divorced from any area of life. Thus, we must embrace mathematics, as it is present in all facets of our lives that we meet on a daily basis. However, in elementary school, there are still many students who dislike mathematics, especially in multiplication. The difficulty learning multiplication arise from the beginning of 3rd grade to 5th grade students, which is influenced by several factors including the teacher's delivery factor with the multiplication material that makes some students cannot digest and students' cognitive abilities. For this reason, the teacher has various ways so that students are able to understand multiplication. The techniques applied by the teacher are memorizing, fast counting with fingers, and so on.